Bo and the Community Garden - Smith, Elliott, 1976-; Bosa, Subi (Minneapolis : Lerner Publications, 2023)
Bo and his friends cannot agree on what to plant in their plot at the school community garden. Can they find a way to work together to help their community?--Back cover.
Bo's world -- An opportunity -- Planting seeds -- Green thumbs.
Keywords: Gardening -- Juvenile fiction; Juvenile fiction; Fiction; Fiction; Early chapter books; Early chapter books; Fiction